Studying the reproduction-biological effect of the GPR54 receptor gene in sheep - Szabó, Szilvia; Árnyasi, Mariann; Jávor, András (Acta Agraria Debreceniensis, 2007)
One of the main economical problems of sheep breeding is that continual production is not possible due to the seasonality of animals. Today, genes, mutations that may develop aseasonality in sheep are extensively researched in order to make the establishment of populations capable of aseasonal estrus possible.According to the current knowledge, the GPR54 gene participates in the GnRH release from the hypothalamus, and thus in the alteration of the reproduction state of the organism. Our research is aimed to determine whether the GPR54 gene has allele variations that influence the proneness to aseasonal estrus in sheep in a different extent. Therefore, the GPR54 gene sequence of sheep is first examined.